Os tons valorativos e a carnavalização nas tiras de humor de Um Sábado Qualquer - Oliveira, Alixandra Guedes Rodrigues de Medeiros e (2022)
To analyze the effects under the development of meaning, valuation and carnivalization from the elaboration of laughter in the humorous comic stories of “Um Sábado Qualquer” (henceforth USQ), created by Carlos Ruas, posted on the social network Instagram, is the main objective of this thesis. For that, we used the concepts of evaluating tone and carnivalization, theorized by Círculo de Bakhtin (2008; 2010; 2014; 2015; 2016), some studies about comic stories as a genre organized by Santos (2002), Ramos (2009; 2013; 2017), Franco (2004; 2013) and McCloud (2005), and the perspectives regarding laughter presented by Minois (2003), Bergson (1900/ 2018), Freud (1905/2017) and Lima (2019). Methodologically, this is an interpretative-qualitative research, based on the documental method. Its corpus is composed of eleven humorous comic stories from USQ. Specifically, we aimed a) to analyze the emotive-volitional tones from the humorous comic stories of USQ under their observed recurrent themes; b) to understand how the constitution of absurd is composed considering the refraction of social problematics through a religious speech; c) to verify which aspects of the carnival cosmovision pervade the USQ comic stories. The conclusions of the analysis showed that the USQ comic stories, posted on the social network Instagram, are formed by concrete utterances full of volitional-emotive tones, ideological-evaluating positions, which reflect and redirect the attitude of the enunciator in relation to what is being enunciated. Absurd in the humorous comic stories emphasizes the movements of valuation and carnivalization from the religious Jewish-Christian speech. Through the redirection of social events and facts from the social imagery, axiological approaches are linguistically and visually materialized in the comic stories. The carnivalized cosmovision occurs through aspects such as the familiar contact, the downgrading, the dethronement and the desecration of an image of the Lord/ Father/ Almighty and the inversion of some biblical figures and events. Hence, the USQ humorous comic stories promote some kind of an upgrade of the main biblical icon, the Lord/ Father/ Almighty, under the character of God, through the desacralization and the carnivalized downgrading, according to what is proposed by Bakhtin (2008; 2015).